2006
DOI: 10.1093/humrep/del297
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of matrix metalloproteinase-9 in the eutopic endometrial tissue of women with endometriosis

Abstract: These findings make plausible the involvement of MMP-9/TIMP-1 imbalance in the invasiveness of the endometrial tissue of patients with endometriosis and the ectopic development of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
66
0
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(84 citation statements)
references
References 41 publications
9
66
0
8
Order By: Relevance
“…Alteration of MMP-9 and MMP-2 is an important factor in the development of endometriosis. [13][14][15][16][17][18] Recent studies have suggested that 2,3,7,8-tetrachlorodibenzo-pdioxin (TCDD) and dioxin-like compounds are important in the development of endometriosis. TCDD is a prototype of the polyhalogenated aromatic hydrocarbons, a family of chemicals that have a common mechanism of action.…”
Section: Introductionmentioning
confidence: 99%
“…Alteration of MMP-9 and MMP-2 is an important factor in the development of endometriosis. [13][14][15][16][17][18] Recent studies have suggested that 2,3,7,8-tetrachlorodibenzo-pdioxin (TCDD) and dioxin-like compounds are important in the development of endometriosis. TCDD is a prototype of the polyhalogenated aromatic hydrocarbons, a family of chemicals that have a common mechanism of action.…”
Section: Introductionmentioning
confidence: 99%
“…Выявлена значитель-но более высокая экспрессия MMP-2 и ММР-9 в эк-топическом и эутопическом эндометрии у женщин с эндометриозом по сравнению с группой контроля [40]. Другие исследования показали, что экспрессия MMP-9, ММР-2, ММР-7 повышена в эндометри-альной ткани, а изменения экспрессии MMP-9 -важный фактор в развитии эндометриоза [39,41,42]. Анализ полиморфизмов генов ангиотензин-1 пре-вращающего фермента (angiotensin I converting enzyme -ACE) и MMP-2 показал отсутствие связи с эндометриозом, в то время как полиморфизмы генов MMP-1, ММР-3 и ММР-9 связаны с высоким ри-ском развития этого заболевания [43].…”
Section: инвазияunclassified
“…Повышенной инвазии способствуют вы-сокий уровень активатора плазминогена и мат-риксных металлопротеиназ (MMPs). В литерату-ре описано повышение активности MMPs 1, 2, 3, 7, 9, 10 при эндометриозе, причем уровень фер-ментов возрастает с увеличением тяжести и рас-пространенности заболевания; а также отмечен пониженный уровень экспрессии тканевого ин-гибитора матриксных металлопротеиназ (TIMP), что способствует процессам инвазии эндометри-оидных имплантов [21,67].…”
Section: роль перитонеальных факторов в патогенезе эндометриоза ассоunclassified